Improving hand hygiene measures in low-resourced intensive care units: experience at the Kigali University Teaching Hospital in Rwanda - Mvukiyehe, Jean Paul; Tuyishime, Eugene; Ndindwanimana, Anne; Rickard, Jennifer; Manzi, Olivier; Madden, Gregory R.; Durieux, Marcel E.; Banguti, Paulin R. (International Journal of Infection Control, 2021)
Background: Proper hand hygiene (HH) practices have been shown to reduce healthcare-acquired infections. Several potential challenges in low-income countries might limit the feasibility of effective HH, including preexisting knowledge gaps and staffing. Aim: We sought to evaluate the feasibility of the implementation of effective HH practice at a teaching hospital in Rwanda. Methods: We conducted a prospective quality improvement project in the intensive care unit (ICU) at the Kigali University Teaching Hospital. We collected data before and after an intervention focused on HH adherence as defined by the World Health Organization ‘5 Moments for Hand Hygiene’ and assuring availability of HH supplies. Pre-intervention data were collected throughout July 2019, and HH measures were implemented in August 2019. Post-implementation data were collected following a 3-month wash-in. Results: In total, 902 HH observations were performed to assess pre-intervention adherence and 903 observations post-intervention adherence. Overall, HH adherence increased from 25% (222 of 902 moments) before intervention to 75% (677 of 903 moments) after intervention (P < 0.001). Improvement was seen among all health professionals (nurses: 19–74%, residents: 23–74%, consultants: 29–76%). Conclusions: Effective HH measures are feasible in an ICU in a low-income country. Ensuring availability of supplies and training appears key to effective HH practices.